Long-Term Chronic Intermittent Hypobaric Hypoxia in Rats Causes an Imbalance in the Asymmetric Dimethylarginine/Nitric Oxide Pathway and ROS Activity: A Possible Synergistic Mechanism for Altitude Pulmonary Hypertension? - Nicole Lüneburg; Patricia Siques; Julio Brito; Karem Arriaza; Eduardo Pena; Hans Klose; Fabiola Leon-Velarde; Rainer H. Böger (Pulmonary Medicine)
Chronic intermittent hypoxia (CIH) and chronic hypoxia (CH) are associated with high-altitude pulmonary hypertension (HAPH). Asymmetric dimethylarginine (ADMA), a NO synthase (NOS) inhibitor, may contribute to HAPH. This study assessed changes in the ADMA/NO pathway and the underlying mechanisms in rat lungs following exposure to CIH or CH simulated in a hypobaric chamber at 428 Torr. Twenty-four adult Wistar rats were randomly assigned to three groups: CIH2x2 (2 days of hypoxia/2 days of normoxia), CH, and NX (permanent normoxia), for 30 days. All analyses were performed in whole lung tissue. L-Arginine and ADMA were analyzed using LC-MS/MS. Under both hypoxic conditions right ventricular hypertrophy was observed (p<0.01) and endothelial NOS mRNA increased (p<0.001), but the phosphorylated/nonphosphorylated vasodilator-stimulated phosphoprotein (VASP) ratio was unchanged. ADMA increased (p<0.001), whereas dimethylarginine dimethylaminohydrolase (DDAH) activity decreased only under CH (p<0.05). Although arginase activity increased (p<0.001) and L-arginine exhibited no changes, the L-arginine/ADMA ratio decreased significantly (p<0.001). Moreover, NOX4 expression increased only under CH (p<0.01), but malondialdehyde (MDA) increased (up to 2-fold) equally in CIH2x2 and CH (p<0.001). Our results suggest that ADMA and oxidative stress likely reduce NO bioavailability under altitude hypoxia, which implies greater pulmonary vascular reactivity and tone, despite the more subdued effects observed under CIH.